New records of predaceous midges in Bezzia Kieffer and Phaenobezzia Haeselbarth from Mexico with description of two new species of Bezzia (Diptera: Ceratopogonidae) - Huerta, Herón; Spinelli, Gustavo R.; Jr, William L. Grogan (Zootaxa, 2023)
Two new species of Bezzia Kieffer are described from Mexico, one in the gibbera group, B. (Bezzia) trujilloi sp. nov. from the state of Veracruz, and the other in the glabra group, B. (Homobezzia) breidenbaughi sp. nov. from Lagunas de Zempoala National Park nature reserve, state of Mexico. Two new country records of B. (Bezzia) mesotibialis Spinelli & Wirth from Veracruz and B. (Homobezzia) snowi Lane from Guerrero and Oaxaca, and the following new state records are also included: B. (B.) gibbera (Coquillett), B. (B.) hondurensis Spinelli & Wirth, B. (B.) punctipennis (Williston) from Veracruz; B. (H.) pulchripes Kieffer and Phaenobezzia maya Spinelli & Wirth from Yucatan; B. (H.) venustula (Williston) and Phaenobezzia fulvithorax (Malloch) from Guerrero; Phaenobezzia fulvithorax (Malloch) from Morelos and B. (H.) venustula (Williston) from Oaxaca. A key to Bezzia species from Mexico is also included.